Igniting Intrapreneurial Sparks: Transforming Non-Business Students through Constructivist ENTRE Learning at Universitas Negeri Medan - Ali Fikri Hasibuan; Aprinawati Aprinawati; Joko Suharianto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The development of entrepreneurship teaching materials tailored for non-entrepreneurship study programs is a strategic approach to fostering entrepreneurial mindsets and skills among students from diverse academic disciplines. This study aimed to design and evaluate entrepreneurship teaching materials based on a constructivist approach, integrating the ENTRE model, which combines theoretical and practical components. Employing a mixed-methods Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the developed module emphasized active learning, problem-solving, and real-world applications, addressing the needs of Community Education students at Universitas Negeri Medan. Validation by experts, practicality assessments by lecturers and students, and effectiveness evaluations through learning outcome tests and interviews demonstrated that the module was valid (average score 4.2), practical (average score 4.0), and effective (test score improvement p < 0.001). Qualitative findings revealed enhanced engagement, creativity, and entrepreneurial mindset transformation, overcoming initial challenges such as unfamiliarity with business terminology. This study provides a framework for integrating entrepreneurship education into non-entrepreneurship curricula, promoting intrapreneurial and entrepreneurial competencies relevant to the Indonesian higher education context.